Integration of batch plant design, automation, and operation software tools - Crooks,CA; Kuriyan,K; Macchietto,S (1992)
The integration of three existing general purpose software packages for optimal design and scheduling, production management, and operating procedure synthesis is demonstrated. The issues involved, some practical results, and the benefits obtained are discussed with reference to an industrial example. Such benefits include reduced engineering time, consistent models of both the process and the plant, and re-usability of the models. (from Authors)